Fast Fashion Frenzy : Exploring The Impact of Store Atmosphere on Impulsive Buying - Faiza Naomi, Siti Mayla; Gatot Nazir Ahmad; Nofriska Krissanya; Terrylina Aryinta Monoarfa, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The purpose of this study was to analyze the effect of store atmosphere, discounts and hedonic shopping value on positive emotions in the formation of impulsive buying in fast fashion industry retailers. Impulsive Buying which is an unplanned purchasing behavior that is often driven by emotional factors is an important phenomenon among Gen Z who are the main target audience of fast fashion industry retailers. This study uses a quantitative approach with a survey design, with a target respondent of 250 people domiciled in Jakarta who have purchased fast fashion products at least twice in the last six months. Data were collected using a six-point Likert scale-based questionnaire and analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM). 1) store atmosphere has a significant effect on impulsive buying 2) store atmosphere has a significant effect on positive emotions 3) discounts have a significant effect on positive emotions 4) discounts have a significant effect on impulsive buying 5) hedonic shopping value has a significant effect on positive emotions 6) hedonic shopping value has a significant effect on impulsive buying 7) positive emotions have a significant effect on impulsive buying. This study provides theoretical contributions to marketing science and the fast fashion industry to develop effective strategies to leverage consumer emotional factors to increase impulse buying in a competitive market.